معدل انتشار نخور الطفولة المبكرة عند الأطفال بين عمر 3-5 سنوات في مدينة اللاذقية - نورالله عبد الوهاب (Latakia University Journal -Medical Sciences Series, 2019)
حدثت تحولات عالمية واسعة خلال العقود الأخيرة في نمط الغذاء تضمنت زيادة استهلاك الدسم والسكريات، كما أن المسوحات أظهرت أن تبدل النمط الغذائي أصاب مجتمعات الوطن العربي أيضاً. دلت الدراسات على أن غنى النمط الغذائي بالسكريات في مرحلة الطفولة المبكرة و اليفاعة يسبب ارتفاعاً في معدل حدوث و انتشار النخور في الأسنان المؤقت. تهدف هذه الدراسة إلى تحديد درجة انتشار نخور الطفولة المبكرة و درجة حدتها عند أطفال مدينة اللاذقية بين عمري 3- 5 سنوات. فحصت عينة عشوائية مؤلفة من 400 طفل بعمر 3-5 سنوات ضمن 20 روضة من رياض الأطفال في مدينة اللاذقية باستخدام معايير التشخيص الميداني لنخور الأسنان المستخدمة في الدراسات الوبائية. أظهرت النتائج أن 77.5% من الأطفال المفحوصين مصابون بنخور الطفولة المبكرة، كما كانت قيمة مؤشر dmft 4.25 (± 4.24)، و قيمة مؤشر dmfs 9.37 (± 7.20)، و هي معدلات عالية تحتاج للتحرك على المستوى المحلي و القطري. Throughout the past decades, public nutrition patterns have shifted towards consuming more fat and carbohydrates (especially sugars). Many public surveys have shown that these nutrition pattern changes affect Arab communities, too. Relevant studies show that sugar rich nutrition pattern during early childhood period leads to high caries incidence and prevalence in primary dentition. The aim of this study is to calculate the prevalence and intensity of early childhood caries in a sample of 400 children (aged 3-5-years) randomly selected from 20 kindergartens in Lattakia, using caries diagnosis criteria for epidemiological studies. The results show that 77.5% of the examined children have early childhood caries. The dmft index is 4.25 (± 4.24), and the dmfs index is 9.37 ±) 7.20(; these values are considered very high, which calls for a national program of prevention at all levels, and for offering dental facilities for treating affected children.